HEGEMONY OF PERFORMANCE ACCOUNTABILITY SYSTEMS OF GOVERNMENT INTITUTIONS IN MALANG : AN IDEOLOGY PERSPECTIVE - Ratna Dwi Nastiti; Sri Pujiningsih; Cipto Wardoyo (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2021)
This study aimed to understand how the ideology of Gramsci hegemony thought be internalized into implementation and evaluation of Performance Accountability System of Government Institution (SAKIP) in Malang. This study was qualitative research by using a critical case study approach. Data collection of research was conducted by several techniques such as observation, semi-structured interview, and documentation with a key informant and several supporting informants. Data analysis in this study was thematic data analysis where it was used to identify and analyze the meaning pattern in a data set. The result of the study showed that ideology had an important role in maintaining hegemony in the implementation and evaluation of SAKIP in Malang. Ideology was internalized through a continuous socialization process, desk, and technical guidance that created awareness and fairness thus it formed a hegemonic culture. The results were expected to able to contribute theoretically, strengthening and enriching the theory of hegemony in the implementation and evaluation of SAKIP. In addition, the results of this study were expected to contribute practically to the Central Government's policies related to the implementation and evaluation of SAKIP that did not burden local governments.